Patterns of recovery in catastrophically disturbed reef fish assemblages - Halford, Andy; Perret, J. (Inter-Research, 2009)
Direct and lethal natural disturbances to coral reef fish assemblages are rare, as the fishes mobility usually allows for rapid migration away from such events. However, in 1989 and again in 2002, coral spawn ‘slicks’ off Coral Bay in Western Australia caused many reef organisms to be asphyxiated resulting in catastrophic mortality. A survey in 2002 revealed significant recovery of hard corals within the area disturbed in 1989 (6 to 32%), but little recovery of the fish assemblages with their structure being highly skewed towards herbivorous species. The lack of recovery in the fish assemblages was unexpected for 2 reasons: (1) the existence of healthy fish populations in adjacent areas and (2) the well-known positive association between many species of reef fish and their benthic habitat. We identified a combination of minimal recruitment to the disturbed area of the bay and a significantly changed coral community structure to be likely causes of the prolonged recovery process. Although just as lethal to the reef community, the 2002 disturbance was significantly smaller and patchy in its extent. In contrast to the 1989 event, the overall effects of this smaller disturbance were positive with species richness and abundance of fish increasing during the weeks after the event, primarily via migration from nearby areas of reef. Together, these results demonstrate the importance of scale when defining disturbance outcomes on coral reefs and highlight the significant role that ‘local’ factors can play in mediating outcomes from disturbance. This type of information is especially pertinent to reef managers trying to formulate effective plans for conservation of their local reef systems.